2009
DOI: 10.1557/proc-1210-q03-15
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Sputtering of Magnesium Hydride Thin Films for Photovoltaic Applications

Abstract: Deposition of MgHx (MgH2 + Mg) thin films is performed using RF reactive sputtering in argon-hydrogen plasma. Films are characterized using x-ray diffraction (XRD), scanning electron microscopy, optical and resistivity measurements. Formation of crystalline MgH2 is confirmed by XRD, but the formation of some metallic Mg in the films could not be avoided. Increased H/Mg ratio by deposition at high hydrogen flow or high total pressure gives films that oxidize within days or weeks. Deposition at elevated substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The latter sulfurized S-free CIGSe absorbers in H 2 S before the buffer deposition, which emphasizes the importance of S in interface formation found in the present study. Platzer-Björkman et al obtained 16% conversion efficiency of solar cells back in 2003 15) and 16.4% later in 2006. 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter sulfurized S-free CIGSe absorbers in H 2 S before the buffer deposition, which emphasizes the importance of S in interface formation found in the present study. Platzer-Björkman et al obtained 16% conversion efficiency of solar cells back in 2003 15) and 16.4% later in 2006. 17…”
Section: Resultsmentioning
confidence: 99%
“…One promising alternative buffer layer material for achieving a high conversion efficiency of the respective solar cells and modules is Zn(O,S), which may be deposited by, e.g., CBD, 2,5,6) magnetron sputtering, [7][8][9][10][11][12][13][14] or atomic layer deposition (ALD). [15][16][17][18][19][20] CBD of Zn(O,S) buffer layers is already applied in highly efficient solar cells 2,6) but this technologyin comparison with sputtering and ALDoffers limited options for the deliberate adjustment of [S]= ([S]+[O]) (SSO) ratios. Studies on this topic using sputtering and ALD methods have shown that there seems to be an optimal range of the SSO ratio, at least for the particular sample under investigation.…”
Section: Introductionmentioning
confidence: 99%